Bibliografía sobre John Dewey: Filosofía de la Educación - Fermoso, Paciano (Teoría de la Educación. Revista Interuniversitaria, 2009)
In this article the autor selects the J. Dewey's original writings and the most important bibliography about his educational thought. Before his writings and before the general bibliography are a brief biography, and introduction to his philosophical thought, his main philosophical works and some monographic studies about his philosophical conception. His tehoric/philosophical educational thought and his educational writings are the first essence of this deweyian bibliography. In the last section ar classified in seven paragraphs all books and articles about the educational thought of J. Dewey: general studies and repertoires; foundatios of his educational theory; philosophy and education; his influence in the educational world; monographic studides; relations with the philosophical systems; and others.